2020
DOI: 10.1038/s41467-020-14923-8
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal inflammation influences but does not arrest rapid immune development in preterm babies

Abstract: Infection and infection-related complications are important causes of death and morbidity following preterm birth. Despite this risk, there is limited understanding of the development of the immune system in those born prematurely, and of how this development is influenced by perinatal factors. Here we prospectively and longitudinally follow a cohort of babies born before 32 weeks of gestation. We demonstrate that preterm babies, including those born extremely prematurely (<28 weeks), are capable of rapidly ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 42 publications
5
19
0
Order By: Relevance
“…Additionally, many of the intracellular immunologic features we identified as variable with respect to GA are not known to be directly affected by glucocorticoids, and some trends, such as elevated MAP-kinase/NFkb baseline signaling, are counter to the expected effect of glucocorticoids (93). It should also be noted that umbilical cord blood provides a snapshot of the immune system at the time of birth but may not reflect the post-natal immune profile (29,94). Nonetheless, several smaller studies have suggested that the immune status at the time of birth correlates with the development of later morbidity and mortality, so cord blood remains a clinically relevant sample (21)(22)(23)(24)26).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, many of the intracellular immunologic features we identified as variable with respect to GA are not known to be directly affected by glucocorticoids, and some trends, such as elevated MAP-kinase/NFkb baseline signaling, are counter to the expected effect of glucocorticoids (93). It should also be noted that umbilical cord blood provides a snapshot of the immune system at the time of birth but may not reflect the post-natal immune profile (29,94). Nonetheless, several smaller studies have suggested that the immune status at the time of birth correlates with the development of later morbidity and mortality, so cord blood remains a clinically relevant sample (21)(22)(23)(24)26).…”
Section: Discussionmentioning
confidence: 99%
“…Preterm infants who had an inflammatory insult, however, have reduced percentages of CXCL8 but comparable levels of TNF-producing T cells, as precursors of adverse outcome. Hence, distinct identifiable differences in functionality may predict subsequent infection-mediated outcomes [43]. Intriguingly, there is evidence that the developing organ systems at risk for long-term sequelae have a significant cross talk via the microbiome-immune interaction (gut-brain axis, gutlung axis, gut-heart axis) [44].…”
Section: Sustained Inflammation In the Context Of Preterm Birthmentioning
confidence: 99%
“…Preterm infants have been suggested to have a skewed T h 2 response based on their increased production of a classical T h 2 cytokine, IL-5, and decreased production of a T h 1 cytokine, IFN-γ, upon stimulation of peripheral blood compared to term cord blood (7). Postnatally, the ability of preterm T h cells to secrete IFN-γ remains low with single cell RNA-seq analysis of term and preterm infants at 12 weeks of age demonstrating up-regulation of genes that suppress IFN-γ, together with longitudinal sampling of preterm infants displaying low expression (6,13). An effective T h 1 response is key to preventing intracellular infections, including bacteria, and this may explain why preterm infants have increased susceptibility.…”
Section: Skewing Of the T-helper (T H ) Responsementioning
confidence: 99%
“…γδ T cells develop a memory phenotype in the first month of life (15) and preterm γδ T cells have an increased ability to secrete IFN-γ and IL-10 upon stimulation with PMA and ionomycin compared to both term γδ T cells and preterm αβ T cells (15). The ability to secrete IFN-γ increases over time, which is in contrast to preterm T h cells (13). However, when challenged with influenza virus, cord blood γδ T cells show a decreased ability to proliferate and produce IFN-γ compared to term infants and adults (14).…”
Section: Gamma-delta (γδ) T Cellsmentioning
confidence: 99%